PERBANDINGAN KINERJA PEGAWAI BERDASARKAN GENDER PADA DINAS PERTANIAN PANGAN DAN PERIKANAN KOTA TANJUNGPINANG - Satriadi Satriadi; Nur Mona Oktavia; Dwi Vita Lestari Soehardi; R. Rudi Alhempi (Jurnal Inovasi Penelitian, 2021)
This study aims to known the comparison of performance between Men and Women employees on Dinas Pertanian Pangan dan Perikanan Tanjungpinang City. This type of study using descriptive quantitative methods with comparative’s technique. Data collection technique using observation, questionaire, and library study. The population of this study is 75 people. The sample of this study is 60 people that constructed by 30 men and 30 women. The result of independent t-test, Sig. (2- tailed) values is 0,383 > 0,05 its mean there is no significant different between men and women employee performance. The conclusions of this study is different performance between employee man and woman would be seen based on average performance value of men is 82,5 and the average performance value of women is 80,7. The difference of these averages performance’s value is close by 1,8 point so its seems both of them is no significant different about the performance. Different performance between employee men and women reconfirmed in the result of independent t-test, the Sig. (2-tailed) value is 0,383 > 0,05 its mean there is no significant different between men and women employee performance or H2 was accepted and H1 was declined.